Epidemic of wild-origin H1NX avian influenza viruses in Anhui, China - Ye Ge; Qiu-Cheng Yao; Xian-Fu Wang; Zhi-Qiang Fan; Guo-Hua Deng; Hong-Liang Chai; Hua-Lan Chen; Yu-Ping Hua (Infectious Diseases of Poverty, 2017)
Abstract Background As the natural hosts of avian influenza viruses (AIVs), aquatic and migratory birds provide a gene pool for genetic transfer among species and across species, forming transient “genome constellations.” This work describes the phylogenetic dynamics of H1NX based on the complete molecular characterization of eight genes of viruses that were collected from 2014 to 2015 in Anhui Province, China. Methods Hemagglutination and hemagglutination inhibition tests were used to determine the hemagglutination (HA) activity of the HA subtypes. The entire genomes of the viruses were sequenced on an ABI PRISM 3500xl DNA Analyzer. The sequences were genetically analysed to study their genetic evolution using DNASTAR and MEGA 6. The pathogenic effects of the viruses were evaluated using mouse infection models. Results Seven strains of the H1 subtype avian influenza virus were isolated. Phylogenetic analysis indicated natural recombination of the H1 influenza viruses between the Eurasian lineage and the North American lineage. Some genes had high sequence identity with A/bean goose/Korea/220/2011(H9N2), which is a typical case involving viral reassortment between the Eurasian lineage and the North American lineage. The results of infection experiments in mice showed that the viruses could acquire the ability to multiply in mouse respiratory organs without adaptation. Conclusions These findings suggest that continued surveillance of wild birds, particularly migratory birds, is important to provide early warning of possible H1 influenza epidemics and to understand the ecology of the virus.